Occurrence of Vibrio cholerae Non 01 and Their Dispersion Phenomena in the Coastal Waters at Mangalore - S., Sreeja; O., Raveendran (Fishery Technology, 2025)
Occurrence of Vibrio cholerae non 01 and their dispersion in the coastal waters of Mangalore for three seasons were studied. The near-shore stations recorded comparatively higher incidence of these bacteria while places with a depth of 10m, 2 to 3 kilometres away from the shore, showed a gradual diminishing trend and at the offshore stations, 5 to 6 kilo metres away from the shore, the abundance of the organism was very low. Environmental parameters like salinity, temperature and pH and their correlation with the occurrence of this species are discussed.